2022
DOI: 10.1055/s-0042-1757460
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Action of Qihuang Jiangtang Capsule in the Treatment of Type 2 Diabetes Based on Network Pharmacology and Molecular Docking Technology

Abstract: Objective Our objective was to investigate the potential mechanism of action of Qihuang Jiangtang capsule (QHJTC) in the treatment of type 2 diabetes mellitus (T2DM) through network pharmacology and molecular docking. Methods The active components of materia medica in the formula of QHJTC were searched on the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform and Encyclopedia of Traditional Chinese Medicine. The targets related to the active components were obtained via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…By constructing a "drug-component-potential target" network, genkwanin, acacetin, apigenin, and quercetin were identified as having higher Degree values, indicating their significant role in the treatment of AP with SHG. [23,24] Genkwanin, a methoxyflavone, has been found to possess potent anti-inflammatory effects by inhibiting inflammatory mediators and pathways. [25] Studies have demonstrated that genkwanin can exhibit anti-inflammatory activity by activating B-cell nuclear factor kappa light chain enhancer (NF-κB), nuclear factor erythroid 2-related factor, and transcriptional signal transducer and activator.…”
Section: Discussionmentioning
confidence: 99%
“…By constructing a "drug-component-potential target" network, genkwanin, acacetin, apigenin, and quercetin were identified as having higher Degree values, indicating their significant role in the treatment of AP with SHG. [23,24] Genkwanin, a methoxyflavone, has been found to possess potent anti-inflammatory effects by inhibiting inflammatory mediators and pathways. [25] Studies have demonstrated that genkwanin can exhibit anti-inflammatory activity by activating B-cell nuclear factor kappa light chain enhancer (NF-κB), nuclear factor erythroid 2-related factor, and transcriptional signal transducer and activator.…”
Section: Discussionmentioning
confidence: 99%